Aging effect on the mixed-mode (I/III) fracture toughness of cement emulsified asphalt composite: Experimental and statistical investigation. (1st April 2022) - Najjar, Shima; Mohammadzadeh Moghaddam, Abolfazl; Sahaf, Ali; Aliha, M.R.M.
Highlights: Aging effect on the mixed-mode fracture behavior of CEAM was studied using ENDB sample. Mix designs and fracture behavior were produced and predicted by Response Surface Method. Aged and unaged sample showed the highest and lowest toughness in mode I and III, respectively. A/C and A/C*W/C showed significant effect on stress intensity factor of all mode mixities. Aging decreases critical stress intensity factor in all mode mixities but in different amounts. Abstract: Aging can affect the fracture behavior of bitumen-containing composites due to an increase in the total stiffness of the material. In this study, the effect of aging on the behavior of Cement Emulsified Asphalt Mortar (CEAM) under the mixed-mode I/III fractures was investigated at an intermediate temperature, and its fracture behavior was modeled with the aid of Response Surface Methodology (RSM). To collect the experiential data, several mix designs with different cement contents (C: [460, 500] kg/m 3 ), bitumen-to-cement ratios ( A/C : [0.3, 0.5]), and water-to-cement ratios ( W/C: [0.4, 0.6]) were generated by Central Composite Circumscribed (CCC) method. Then, a series of fracture tests were performed on aged and unaged Edge Notched Disc Bend (ENDB) specimens. The results showed that for both aged and unaged (control) specimens, the highest fracture toughness is obtained under pure tensile mode and by increasing the contribution of mode III the corresponding value of fracture toughness decreases. The developed statistical models revealed that for unaged specimens, the increase in the A/C ratio has a significant effect on the stress intensity factors of mode I, mode III and mixed-mode I/III. However, for aged specimens, the effect of A/C is significantly observed in its interaction with W/C . The effect of aging on the fracture toughness of mortar was also measured with an index called the ratio of Aged to Unaged Fracture Toughness (FTR i Aged/Unaged ). The results showed that aging decreases the critical stress intensity factor of the mortar in the mode mixities, with the highest decrease of 15% under pure mode I.